Ros-Dependent Apoptotic Effect Of Washingtonia Filifera H. Wendl. Extracts On Human Breast Cancer Cell Mcf-7 (Applied Biological Research, 2022)
Washingtonia filifera has many health benefits, but its activity against  cancer cell lines has not yet been explored. The present study assessed the  cytotoxicity of different solvent extracts of W. filifera using MTT  assay. Fluorescence microscopy was used to evaluate apoptosis and  oxidative stress. Only two extracts showed dose- and time-dependent  decrease in cell survival. The ethyl acetate extract of W. filifera (WFET)  exhibited maximum cytotoxicity against HUVECs, MCF7, HCT116, and  HepG2 cells with IC50 values of 21.7, 48.8, 85.8, and 100.6 µg mL-1,  respectively, 24 h post-treatment. Similarly, methanolic extract of W. filifera (WFME) showed maximum cytotoxicity against HUVECs (IC50: 21.8 µg  mL-1) cells, followed by MCF-7 (73.3 µg mL-1), HCT116 (98.5 µg mL-1), and  HepG2 (100 µg mL-1). Light and florescent microscopy using 4′,6- diamidino-2-phenylindole, and acridine orange-ethidium bromide dyes showed apoptotic cell death. Intracellular reactive oxygen species (ROS)  was evaluated using DCFH-DA dye. The WFET and WFME extracts showed  increased intracellular ROS with increased concentrations of the two  extracts using MCF7 cells. Overall, the WFME and WFET extracts could  hemo-preventive agents against breast carcinoma cells.
Keywords: Apoptosis; anticancer; extract; fluorescent microscopy; ROS; Washingtonia filifera